Artificial intelligence and technologies: challenges for the development of teaching skills in education in Mozambique (PerCursos, 2024)
Artificial intelligence (AI) is an area of computing that since its origin has been concerned with manipulating computers in an intelligent way, that is, making them possess capabilities and abilities that were previously the responsibility of human beings. In this sense, it is important that the teacher, as a learning facilitator, makes use of this intelligence in order to make the teaching and learning process more dynamic, interactive and collaborative, as well as disseminate relevant information to his students according to their interests and desires. This work aims to reflect on the challenges for developing teaching skills in the use of AI and technologies in education in Mozambique. This is qualitative research, with the aim of assisting education professionals, specifically teachers, in developing skills for the use of AI in education. To collect data, bibliographic and documentary research was used. In Mozambique, AI is still a major challenge for all sectors, including education, highlighting the lack of educational systems that use AI technologies, the lack of adequate infrastructure to support this technology, limited access to the Internet and the lack of qualified teachers for its use. Therefore, the establishment of partnerships with other countries that have already implemented AI in education to support the teaching and learning process is considered, as a strategy for the materialization of this process, and to train teachers with a view to developing digital skills for the use of AI.
Keywords: artificial intelligence; technologies; digital competence; teacher